Literature Analysis Trends and Challenges in Corporate Sustainability Management - Nailin Nikmatul Maulidiyah; Asri Kunda; Riyan Andni (Rey Media Grafika, 2024)
Corporate sustainability management has become a critical issue in the modern business environment, driven by increasing global awareness of the environmental, social, and economic impacts of business activities. This study explores the trends and challenges faced by companies in implementing sustainability policies and the role of technology in supporting these efforts. Using a literature review methodology, the study analyzes various sources published from 2020 to 2023, focusing on the integration of sustainability principles in business strategies. The results show that companies are increasingly adopting sustainable practices in the environmental, social, and economic dimensions, with a particular emphasis on social sustainability and the use of digital technologies such as the Internet of Things (IoT) and big data. However, challenges such as the alignment of economic and sustainability goals, lack of data and measurement tools, and the need for supportive government policies remain significant barriers. The study concludes by offering recommendations for companies to adopt a holistic approach, invest in technology, improve data measurement, and foster collaboration with stakeholders to enhance the effectiveness of sustainability efforts.